Spectroscopic properties of inorganic and organometallic compounds : techniques, materials and applications - Yarwood, J.; Douthwaite, R.; Duckett, S. B.; Royal Society of Chemistry (Great Britain) (Cambridge, UK : RSC Pubs, 2009)
42